EFEK PEMBERIAN LARUTAN DIAZINON PER ORAL TERHADAP KERUSAKAN SEL-SEL TUBULI GINJAL MENCIT - Saikhu Akhmad Husen; J. Soemartojo; S. Soekamto M (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1996)
One of the pesticide which very common to protect plants from the pest is diazinon. But this pesticide contain neurotoxic organophosphate bound. The organophosphate bound has also an effect on kidney's tissue. Recently the research about effect of diazinon still required. The study was carried out to observe the effect of diazinon on cells of tubuli renalis in mice. This study was used 30 mice, by random sampling became 6 goup. Three groups for controle (K1, K2, and K3) and three groups for treatment (P1, P2, and P3). The controle groups were given 0.5 ml aquadest and the treatment groups were given 150 ppm of 0.5 ml diazinon solution up to 10, 20, and 40 days for P1, P2, and P2 sub sequently. The result showed that the effect of diazinon solution given per oral for the difference time were caused difference demage level on cells ob the tubuli renalis in mice. Keywords : diazinon, cells of tubuli renalis